Foodborne hazards in food in Burkina Faso, 1990–2019: A systematic review and meta-analysis - Dinede, Getachew; Amenu, Kebede; Alonso, Silvia; Gazu, Lina; Mutua, Florence K.; Roesel, Kristina; Lindahl, Johanna F.; Sousa, F.M.; Ulrich, P.; Guadu, T.; Dione, Michel M.; Ilboudo, Guy S.; et al. (Frontiers Media, 2023)
Background: Foodborne diseases impose substantial public health burden and jeopardize socio-economic development worldwide. While accurate information on foodborne hazards is needed for informed decision in food safety interventions, such information is scarce in developing countries such as Burkina Faso. We conducted a systematic review and meta-analysis of studies reporting foodborne hazards in foods in Burkina Faso to describe the present knowledge of the situation.